2006
DOI: 10.1002/ejic.200600561
|View full text |Cite
|
Sign up to set email alerts
|

Copper/Zinc L‐Tartrates: Mixed Crystals and Thermolysis to a Mixture of Copper Oxide and Zinc Oxide That Is Catalytically Active in Methanol Synthesis

Abstract: The system consisting of copper/zinc L-tartrate mixed crystals has been systematically explored in the whole range from pure copper tartrate to pure zinc tartrate. Mixed crystal L-tartrates were prepared and their thermochemical behaviour under oxygen was investigated. Oxidic precatalysts (CuO/ZnO) for catalytic tests in methanol synthesis were prepared by mild thermolysis of the mixed tartrates in air at 300°C. Catalytic tests were performed with a multi-channel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These include the combustion of organic metal salts [17,15,18,19], mechano-thermal [20], sol-gel [21,22] and colloidal synthesis [23]. In addition, low-metal-loading catalysts have been prepared by impregnation or chemical vapour deposition of Cu and Zn precursors on high surface area supports [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…These include the combustion of organic metal salts [17,15,18,19], mechano-thermal [20], sol-gel [21,22] and colloidal synthesis [23]. In addition, low-metal-loading catalysts have been prepared by impregnation or chemical vapour deposition of Cu and Zn precursors on high surface area supports [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The Bragg peak positions for ZnC 4 H 4 O 6 were obtained by digitising data from Fig. 1 of reference [30]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[6,8,11,14,[21][22][23] We have recently shown that active catalysts can also be prepared by thermolysis of bimetallic coordination compounds, [24] xerogels and aerogels, [25] and tartrate mixed crystals. [26] Copper nanoparticles in liquid dispersion were recently shown to be active as methanol catalysts, [27] as well as metal-loaded mesoporous silicates [28] and metal-oxide frameworks (MOFs). [29] Here we report on the preparation, characterization and catalytic activity of ZnO and CuO/ZnO nanocomposites which were obtained by a combination of sol-gel synthesis and photochemical oxidation which was applied earlier to cific surface area of about 110-130 m 2 g -1 (probably due to both silica and nanocrystalline CuO/ZnO) and the good catalytic activity in methanol synthesis from CO/CO 2 /H 2 synthesis gas (7 to 37 %, compared to an industrial standard methanol catalyst).…”
Section: Introductionmentioning
confidence: 99%